2015
DOI: 10.1002/2015gb005144
|View full text |Cite
|
Sign up to set email alerts
|

Leaky nitrogen cycle in pristine African montane rainforest soil

Abstract: ). This study provided new process understanding of soil N cycling in humid tropical forests and added geographically independent evidence that humid tropical forests are characterized by soil N dynamics and N inputs sustaining bioavailable N loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 60 publications
2
14
1
Order By: Relevance
“…Gross N mineralization for the karst forest was only measured at one site (Zhu et al, ), which showed comparable rates with the current study. Compared with other subtropical/tropical regions of the world, gross N mineralization rates in the present study were higher than those (0.6–1.8 mg N kg −1 d −1 ) observed in forest soils of subtropical Australia (Burton et al, ) but were at the lower end of the range (2–14 mg N kg −1 d −1 ) reported for tropical forests (Rutting et al, ; Silver et al, , ; Sotta et al, ).…”
Section: Discussioncontrasting
confidence: 73%
“…Gross N mineralization for the karst forest was only measured at one site (Zhu et al, ), which showed comparable rates with the current study. Compared with other subtropical/tropical regions of the world, gross N mineralization rates in the present study were higher than those (0.6–1.8 mg N kg −1 d −1 ) observed in forest soils of subtropical Australia (Burton et al, ) but were at the lower end of the range (2–14 mg N kg −1 d −1 ) reported for tropical forests (Rutting et al, ; Silver et al, , ; Sotta et al, ).…”
Section: Discussioncontrasting
confidence: 73%
“…The observations from lowland forest are in stark contrast to the high soil pore water and stream water NO 3 À concentrations observed in the montane forest with comparatively low DON losses. Previous reports have indeed also shown high NO 3 À losses from some Neotropical montane forests, which has led to the belief that many tropical montane forests are not N-limited (Mcdowell and Asbury 1994, Brookshire et al 2012b, R€ utting et al 2014. This is further supported by the lower soil C:N ratio in the montane compared to lowland forest, which is an indicator of higher soil available N (Appendix S1: Table S6).…”
Section: Comparing Lowland and Montane Mixed Forest (Lmf Vs Mmf)mentioning
confidence: 71%
“…, Rütting et al. ). This is further supported by the lower soil C:N ratio in the montane compared to lowland forest, which is an indicator of higher soil available N (Appendix : Table S6).…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates a recent finding of very high N losses at 1900 m a.s.l. at the Rwanda site (Rütting et al, 2014), and the observation of high retention potential of bio-available N in Chilean Andisols (Huygens et al, 2008). Further research is needed to explain the notable divergence in soil and foliage δ 15 N along the Ecuadorian transect, mainly driven by the highest elevational cluster.…”
Section: Discussionmentioning
confidence: 98%